Sea level VO2max fails to predict VO2max and performance at 1800 m altitude - Roberts, A. D.; Daley, P. J.; Martin, D. T.; Hahn, A.; Gore, C. J.; Spence, R. (Medicine & Science in Sports & Exercise, 1998)
Australian male cross-country ski team members (N = 9) completed simulated multi-staged time trials in an environmental chamber under two conditions; oxygen enriched (sea level) or nitrogen enriched (1800 m) atmospheres. The altitude simulation was not in an acclimatized state. At maximum effort there were significant differences in VO2max (70.2 versus 61.7 ml/kg/min), arterial pO2, and SaO2 but not in heart rate, ventilation, or lactate between the sea level and altitude conditions. There was a decrease in time-trial performance of 7.6% when in altitude simulation. Sea level measures of VO2max or performance could not predict altitude measures pr results. Some individuals were particularly susceptible to the altitude conditions. Implication: Sea level performance and physiological measures do not predict altitude responses.